Incidence of Renal Injuries in Abdominal Trauma at Al-Kindi Teaching Hospital - Al-Basri, Ridha J.; Alrubiae, Mohammed A.; Mutar, Ali H. (AL-Kindy College Medical Journal, 2012)
Background : The kidneys may be injured in abdominal trauma, both blunt & penetrating. Renal trauma may manifest in a dramatic fashion for both the patient and the clinician. Objectives: To evaluate the incidence, management, morbidity &mortality of renal injury in blunt & penetrating abdominal trauma.Results:The majority o f patients were males (35= 77.8%), the rest were females (10= 22.2%). The average age was 37 years (range= 18-56 years). The most common grades were grade1, grade2 and grade3 (40=88.9%), while 5 patients (11.1%) were grades 4 and 5.The most common associated injuries were liver, spleen, small & large bowels and diaphragm. The mortality was 20% (9 patients). The most common cause of death was multiple organ injuries in 2 patients (4.4%), kidney with injury of a second organ in 6 patients (13.3%), while delayed surgery was the cause in 1 patient (2.2%), while the most common cause of morbidity was wound infection in 5(11.1%) and wound dehiscence in 2 patients (4.4%), a total morbidity is of 7 patients (15.5%).Methods: A retrospective study includes 45 patients sustaining renal injury. These trauma patients were admitted to the casualty department in Al-Kindi Teaching Hospital during the period between 1st June 2006 – 31st May 2007. The patients were analyzed regarding their age, sex, mechanism of injury & grade of injury according to Organ Injury Scaling (OIS) classification of the American Association for the Surgery of Trauma (AAST). Management, morbidity & mortality were also noticed.Conclusion: Renal injuries are not uncommon injuries, but they are less common than other intraabdominal organs e.g. liver, spleen and bowel. Injury grading using the OIS system (liver, spleen and kidney) of AAST is a useful tool for comparison and to evaluate management according to injury grade.